Los efectos directos y colaterales de la disolución de Herri Batasuna - Álvarez Conde, Enrique; Català i Bas, Alexandre H. (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
The banning of Herri Batasuna, Euskal Herritarrok and Batasuna (following the decision of the Spanish Supreme Court adopted the 27th March, 2003) entailed important consequences in the political realm. Firstly, the appearance of several political forces (composed, in fact, by the same agents) which tried to dodge the Organic Law of Political Parties (Ley Orgánica de Partidos Políticos) in the municipal and regional elections of 2003, the elections to the European Parliament in 2004, and the elections to the Basque Parliament of 2005. Secondly, the fierce debate on the dissolution of the political group in the Basque parliament ordered by the Supreme Court on April, 24th 2003. Thirdly, the trial of several members of the Basque parliamentary committee, due to their refusal to comply with the decision of the Supreme Court.